Serum CTRP9 Reflects Coronary Collateralization in Nondiabetic Patients with Obstructive Coronary Artery Disease. (10th March 2022) - Gao, Ang; Liu, Jinxing; Liu, Yan; Hu, Chengping; Zhu, Yong; Zhou, Yujie; Han, Hongya; Zhao, Yingxin
Abstract : Aim. To explore the association between the serum C1q/tumor necrosis factor-related protein 9 (CTRP9) and the formation of coronary collateral circulation in obstructive coronary artery disease (CAD). Methods. A total of 206 patients who underwent coronary angiography at Beijing Anzhen Hospital and had epicardial arteries with at least 95% stenotic lesion were enrolled. Blood samples were taken after an overnight fasting before the coronary angiography. Serum CTRP9 level was measured using commercial enzyme linked immunosorbent assay (ELISA) kit. The development of coronary collateralization was determined according to the Rentrop classification system. Rentrop score 0-1 was graded as impaired or less-developed coronary collateralization (n = 54 ) while the Rentrop score 2-3 was defined as well-developed collateralization (n = 152 ). Results . Serum CTRP9 level was significantly higher in well-developed collateralization and diabetes groups (P < 0.001 ). To further explore the association between the CTRP9 level and coronary collateralization, the enrolled participants were divided into 3 tertiles according to the serum CTRP9 level. The prevalence of impaired coronary collateralization decreased stepwise with the increasing CTRP9 tertiles (P for trend <0.001). Multivariate regression analysis showed that the serum CTRP9 is independently associated with well-developed collateralization, with an OR (95% CI) of 4.49 (1.75-11.55) and 8.98 (2.75-29.35) in the tertiles 2 and 3, respectively. The following subgroup and receiver-operating characteristic (ROC) analysis also indicated that the diagnostic value of serum CTRP9 level for detecting the formation of collateralization persisted only in nondiabetic participants. Lastly, adding the serum CTRP9 into the baseline model could increase the diagnostic value of established model consisting of relevant factor for the discrimination of well-developed collateralization only in the nondiabetic group (P = 0.046 ). Conclusions . Serum CTRP9 reflects well-developed coronary collateralization in nondiabetic patients with obstructive CAD, and CTRP 9   level ≥ 1.217 indicated a greater chance to forming well-developed coronary collaterals.